Evidence-Based Medicine: Ultrasound Guidance for Truncal Blocks. (1st February 2010) - Abrahams, Matthew S.; Horn, Jean-Louis; Noles, L. Michele; Aziz, Michael F.
Abstract : We performed a systematic search of the medical literature and reviewed the evidence examining success rates and incidence of complications of ultrasound (US) guidance relative to traditional techniques for the following blocks: paravertebral, intercostal, transversus abdominis plane, rectus sheath, and ilioinguinal/iliohypogastric. We included studies of sufficient methodologic quality for review and excluded poor-quality studies. We then rated the strength of evidence for US guidance for each block using a system developed by the United States Agency for Health Care Policy and Research. Although relatively few studies have compared US guidance with established techniques, the available evidence suggests that the use of US guidance is a safe and effective means to facilitate correct needle placement and adequate spread of local anesthetic for truncal blocks. Further studies are needed to directly compare US guidance to traditional techniques and to clarify potential benefits and limitations of US guidance for truncal blocks.